78.7k views
4 votes
A quadratic equation has the zeros -3 amd 6. Can the quadratic equation be the given equation? A. (2x + 6)(x - 6) =0. Yes or no B. (6x - 1)(x + 3) =0. Yes or no C. -3x(x - 6) =0. Yes or no

User Felisa
by
5.9k points

1 Answer

2 votes

Answer:

It can be A. (not B or C)

Explanation:

It is A because x-6=0 can be simplified to x=6. Then, 2x + 6, you can divide the whole equation resulting in x+3=0, simplify this and you get x=-3. YES

It is not B because, while x+3=0 results in a zero of -3, 6x-1 can be simplified to be divided by 6. When we do this we get x-1/6=0, which is not equivalent to 6. NO

It is not C because, while x-6=0 results in a zero of 6, -3x can be simplified with the zero product property to get -3x=0 then dividing -3 by 0 giving you 0 which is not equivalent to one. NO

User Anthony Johnston
by
5.8k points